Koncepcja rozwoju kapitalizmu Stanisława Grabskiego - Kundera, Elżbieta (Wydawnictwo Uniwersytetu Wrocławskiego, 2010)
Stanisław Grabski (1871–1949), an economist and politician, approved the thesis that society develops in stages. He adopted holism as a research method and argued that among many factors crucial for development of the society the most important ones are legal and political institutions, as well as the way of the organization of the society. Secondary to the changes of these factors are changes in the economy. He expected that the analysis of the social aspects in economic activities would help him to create universal concept of development of all societies. He was mostly interested in development of capitalism, which proceeded differently in particular countries, undergoing three phases. Grabski emphasized the importance of the fundamental liberal values, which are the basisof the capitalist economy. He proposed reforms to consolidate the rules of liberalism in Poland. He expected them to modernize the economy and increase the social welfare.
Keywords: Grabski, Stanisław (1871-1949); socjalizm historyczny; rozwój kapitalizmu; reformy gospodarcze; II Rzeczypospolita